1981
DOI: 10.1128/aem.41.5.1243-1247.1981
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Systems in Organic Synthesis: Preparative-Scale Resolution of ( R S )-Glaucine by Fusarium solani and Stereospecific Oxidation of ( R )-(−)-Glaucine by Aspergillus flavipes

Abstract: The destructive resolution of (6a R , S )-glaucine (Ic) was accomplished by oxidation of the (6a S )-(+)-enantiomer (Ia), using Fusarium solani ATCC 12823 to yield the unnatural alkaloid (6a R )-(−)-glaucine (Ib). Eighteen cultures were examined for their ability to metabolize the (6a R )-(−)-enantiomer (Ib), and Aspergillus flavipes ATCC 1030 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The routine method of resolving racemic mixtures of these alkaloids, fractional crystallization, is a tedious process. However, the resolution of racemic glaucine (1,2) has been shown to be facile using the microorganisms Fusarium solani (ATCC 12823) and Aspergillus flavipes (ATCC 1030) (10,11). For example, in the microbial transformation of R.S-glaucine (1,2), F. solani stereospecifically and quantitatively converts £-(+)glaucine (1) to dehydroglaucine (3), leaving R-( -)-glaucine (2) as the residual substrate, while A. flavipes stereospecifically and quantitatively converts only R-{~)glaucine (2) to 3, leaving S-(+)-glaucine (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The routine method of resolving racemic mixtures of these alkaloids, fractional crystallization, is a tedious process. However, the resolution of racemic glaucine (1,2) has been shown to be facile using the microorganisms Fusarium solani (ATCC 12823) and Aspergillus flavipes (ATCC 1030) (10,11). For example, in the microbial transformation of R.S-glaucine (1,2), F. solani stereospecifically and quantitatively converts £-(+)glaucine (1) to dehydroglaucine (3), leaving R-( -)-glaucine (2) as the residual substrate, while A. flavipes stereospecifically and quantitatively converts only R-{~)glaucine (2) to 3, leaving S-(+)-glaucine (1).…”
mentioning
confidence: 99%
“…Consequently, these metabolism studies should be repeated with the corresponding C-7 deuterated analogs of glaucine to confirm the results obtained with 7-methyl analogs of the aporphine. We previously have examined the absolute stereochemistry of residual substrates to elucidate the stereochemical course of aporphine dehydrogenation by F. solani and A. flavipes (10,11,18). These experiments with specifically deuterated analogs will not employ the same techniques but, instead, will examine the presence of deuterium in the product as an indication of cisor ¿nzrej-elimination.…”
mentioning
confidence: 99%
“…The use of microbial batch fermentations for the production of specific chemicals is often faster, more economical, and cleaner than chemical synthesis. This has been demonstrated in the production of amino acids (7,13,15) and other chemicals (2,4,5,9,14). We previously reported that Streptomyces viridosporus T7A produces a nonspecific aromatic aldehyde oxidase which catalyzes the oxidation of a variety of aromatic aldehydes to their corresponding carboxylic acids with equimolar uptake, of 02 and production of H202 (3).…”
mentioning
confidence: 98%
“…Several advantages (3,8) of microbial enzymatic conversions have led to the exploitation of microorganisms as catalytic reagents in pollution control, elucidation of structural configurations of chemicals, and establishment of taxonomic characteristics and as analytical tools (2,4,11,18,19). An interesting and significant feature of these reactions is the wide array of intermediates and end products formed from a single compound by varied cometabolic (7,17) or metabolic (1, 6, 9) transformation sequences.…”
mentioning
confidence: 99%